Self-adhesive flexible patches of oxide heterojunctions with tailored band alignments for electrocatalytic H2O2 generation. Issue 47 (15th November 2021) - Khayyam Nekouei, Rasoul; S. Mofarah, Sajjad; Maroufi, Samane; Cazorla, Claudio; O'Mullane, Anthony P.; Yao, Yin; Lim, Sean; Tricoli, Antonio; Sahajwalla, Veena
Abstract : This work reports fabrication of centimetre-size, flexible, self-adhesive ZnO-based heterojunction patches with a tuned electronic band and outstanding electrochemical activity, offering promising alternatives for noble electrocatalysts such as Pt. Abstract : The new class of oxide heterojunctions with mixed dimensionalities holds great promise for energy and environmental applications. However, the existing fabrication strategies typically involve low-yield and multistep processes leading to the formation of powders that necessitate binding agents when used for electrochemical applications; thereby, the durability and performance of the resultant electrode may be adversely impacted. To address these challenges, the present work first reports a high-temperature counter-current gas flow technique for rapid fabrication (5–10 min) of centimetre-size, self-adhesive, free-standing 3D patches made of ZnO-based woven nanowires. Furthermore, the high applicability of the method was shown by layer-by-layer assembly of the ZnO and layers of 0D heteroatoms including Bi2 O3, CdO, SnO2, and carbon forming stratified oxide heterojunction (SOH) nanostructures with midgap states within their electronic bandgap region. This work is innovative in that the ZnO and the fabricated SOHs are synthesised through a sustainable and large-scale method based on microrecycling of waste materials. The engineering of the electronic band positions can modify the functionality of the SOH patches by optimising the potentials required for catalytic reactions. As a representative, the SOH nanostructures were tested for anodic electrocatalytic water oxidation to H2 O2 . The results showed that the ZnO–CdO patch has the lowest overpotential of 150 mV and outstanding stability at 2.33 V vs. RHE. Furthermore, the results of first-principles density functional theory (DFT) calculations (i) confirmed realignments of the band position due to the formation of midgap states, and (ii) revealed that significant improvements in the electrocatalytic H2 O2 performance can be achieved with overpotentials as low as 0.19 and 0.31 V for ZnO–CdO and ZnO–Bi2 O3, respectively. This work offers an ultrafast fabrication strategy to synthesise binder-free SOH nanostructures with an engineered electronic structure that can be an alternative to state-of-the-art noble metal electrocatalysts such as Pt.